ANALISIS KEJADIAN KECELAKAAN KERJA AKIBAT GAS BERACUN MENGENAI TAMBANG BAWAH TANAH: LITERATURE REVIEW - Syahna Azira; Susilawati (CV. ADIBA AISHA AMIRA, 2023)
Mining is the most dangerous occupational sector in the world. Based on statistical data from the Ministry of Energy and Mineral Resources, during 2019 there were mining accidents which resulted in the death of 24 people, 105 workers heavy and 28 workers light. The cause of work accidents in the workforce is related to exposure to underground mining toxic gases. This study used the Systematic Literature Review (SLR) methodology where the data source was obtained from